Informed Decision‐Making in the Context of Prenatal Chromosomal Microarray. Issue 5 (7th March 2018) - Baker, Jessica; Shuman, Cheryl; Chitayat, David; Wasim, Syed; Okun, Nan; Keunen, Johannes; Hofstedter, Renee; Silver, Rachel
Abstract: The introduction of chromosomal microarray (CMA) into the prenatal setting has involved considerable deliberation due to the wide range of possible outcomes (e.g., copy number variants of uncertain clinical significance). Such issues are typically discussed in pre‐test counseling for pregnant women to support informed decision‐making regarding prenatal testing options. This research study aimed to assess the level of informed decision‐making with respect to prenatal CMA and the factor(s) influencing decision‐making to accept CMA for the selected prenatal testing procedure (i.e., chorionic villus sampling or amniocentesis). We employed a questionnaire that was adapted from a three‐dimensional measure previously used to assess informed decision‐making with respect to prenatal screening for Down syndrome and neural tube defects. This measure classifies an informed decision as one that is knowledgeable, value‐consistent, and deliberated. Our questionnaire also included an optional open‐ended question, soliciting factors that may have influenced the participants' decision to accept prenatal CMA; these responses were analyzed qualitatively. Data analysis on 106 participants indicated that 49% made an informed decision (i.e., meeting all three criteria of knowledgeable, deliberated, and value‐consistent). Analysis of 59 responses to the open‐ended question showed that "the more information the better" emerged as the dominant factor influencing both informed and uninformed participants' decisions to accept prenatal CMA. Despite learning about the key issues in pre‐test genetic counseling, our study classified a significant portion of women as making uninformed decisions due to insufficient knowledge, lack of deliberation, value‐inconsistency, or a combination of these three measures. Future efforts should focus on developing educational approaches and counseling strategies to effectively increase the rate of informed decision‐making among women offered prenatal CMA.